Enhancing Science and Social Studies Learning Outcomes Through the Picture and Picture Cooperative Learning Model: A Classroom Action Research in Indonesian Elementary Education - Kurniawati Mengkido; Nashrullah Nashrullah; Muslim AR Muslim AR; Abdul Rahman; Sri Wahyuni (Papanda Publisher, 2026)
Elementary students in IPAS (Integrated Science and Social Studies) often struggle with abstract concepts requiring visual representation and collaborative reasoning. The Picture and Picture cooperative learning model offers a pedagogical approach integrating visual scaffolding with structured group activities. This study examined the effectiveness of the Picture and Picture model in improving Grade V students' learning activities and outcomes in IPAS instruction at SD GKST Talabosa, Indonesia. A two-cycle Classroom Action Research design was employed with 12 fifth-grade students during the 2025/2026 academic year. Data were collected through achievement tests, structured observations of teacher and student activities, and field notes. Analysis combined quantitative measures of mastery levels with qualitative examination of instructional processes. Student engagement increased from adequate (69.23%-72.30%) in Cycle I to very good (81.53%-86.15%) in Cycle II. Teacher performance improved from good (68.42%-75.00%) to very good (76.00%-85.33%). Classical mastery advanced dramatically from 25% at baseline to 66.66% in Cycle I and 100% in Cycle II. Lower-achieving students demonstrated the greatest gains. The Picture and Picture model effectively enhances IPAS learning by combining dual-coding theory, constructivist principles, and social interdependence. The model provides an accessible, low-cost strategy particularly effective in resource-constrained settings, supporting both cognitive development and collaborative competence in elementary science education.